Numerical solution of elastohydrodynamic lubrication with non-newtonian fluid flow - Bahari, Adli (2010)
In this project, a line contact elastohydrodynamic lubrication is modelled through an infinite cylinder on a plane to represent the application of roller bearing. The numerical solution of this problem is presented embedded with free volume model of pressure-viscosity equation using Doolittle-Tait model. Newton-Raphson method is used to solve the Reynolds equation simultaneously with pressureviscosity equation and elastic deformation in order to find the pressure profile and film thickness. The behavior of non-Newtonian fluid also was investigated using power law fluid model. The bearing performances parameters such as pressure, film thickness and friction coefficient of lubricated contacts are calculated. Non-uniform grid also used to improve the pressure spike stability. The results show that the peak pressure increases as the parameters such as velocity, load, material parameter and power law index are increases and the spike is found to shift to the center of roller. The coefficient of friction is reduced as the power law index and slide to roll ratio are decreased.